Evaluation of Creative (Metal) Industry Development Policy in Dealing with the ASEAN Economic Community in Sidoarjo - Berliana Mustika Rani (Indonesian Association for Public Administration, 2017)
Economic Kreatif is one of the progress factors of the national economy. The creative economy concentrates on the economic dynamics of the creative industry sector, which was recently targeted by the government as an area with significant growth potential. On January 20, 2015, President Joko Widodo established a new non-ministerial institution called the Creative Economy Agency (Bekraf). This body is responsible for the expansion of the creative economy in Indonesia. East Java has 29 districts and 9 cities, a number of which host creative industry businesses in the field of SMEs, namely Sidoarjo district. Sidoarjo regency, which is one of the regencies in East Java, is focused on the development of Micro Small Medium Enterprises in facing the ASEAN Economic Community (AEC). The primary creative industry in Sidoarjo district are the Metal Industries in Ngingas Village, Waru Sub-district. The small and medium industry (IKM) metal center of Ngingas, Sidoarjo, East Java is one of the component suppliers for major manufacturing companies in Indonesia. Craftsmen in these industrial centers are constrained by licensing problems. They are also constrained by limited business capital for the procurement of raw materials and production machinery, and the lack of metal waste disposal facilities.